Total versus conventional laparoscopic cyst excision and Roux-en-Y hepaticojejunostomy in children with choledochal cysts: a case–control study - Liu, Fei (BMC Surg, 2020)
BACKGROUND: To compare the efficacy of total and conventional laparoscopic hepaticojejunostomy (TLH and CLH) in children with choledochal cysts (CDCs). METHODS: Data from patients undergoing TLH and CLH between August 2017 and December 2018 were retrospectively analyzed. Intraoperative blood loss, time for jejunum-cojejunum anastomosis, time to oral intake, postoperative hospital stay, hospitalization expenses, and postoperative complications were compared. RESULTS: All 55 patients (TLH = 30, CLH = 25) were successfully treated without conversion to open surgery. In the TLH and CLH groups, the time to oral intake was 3.57 ± 0.19 d and 4.56 ± 0.27 d, respectively (t = 3.07, P < 0.01), the postoperative hospital stay was 5.50 ± 0.28 d and 7.00 ± 0.74 d (t = 2.03, P < 0.05), and the hospitalization expenses were CNY 40,085 ± 2447 and CNY 26,084 ± 2776 (t = 3.79, P < 0.001). There were no significant differences in intraoperative blood loss (9.57 ± 3.28 ml vs 8.2 ± 1.13 ml, t = 0.37, P = 0.72) or time for jejunum-cojejunum anastomosis (80.5 ± 2.46 min vs 75.00 ± 2.04 min, t = 1.68, P = 0.10). The median follow-up periods of the TLH and CLH groups were 17 and 16 months, respectively. Overall complication rates were comparable between the two groups (10% vs 8%, χ(2) = 0.07, P = 0.79). CONCLUSIONS: TLH in children with CDCs has the advantages of rapid gastrointestinal functional recovery and a short hospitalization. However, hospitalization is relatively expensive.